ANALISIS PERBANDINGAN METODE SIMPLE ADDITIVE WEIGHT (SAW) DAN WEIGHT PRODUCT (WP) PENERIMAAN BANTUAN SISWA MISKIN DI SMK N 1 GADINGREJO - Wahyurial, Achmad; Muslihudin, Muhamad; Susanto, Ferry (YHMM PUBLISHING, 2023)
Assistance for underprivileged students is called the Poor Student Assistance (BSM) which is government assistance in the form of cash given directly to students who come from poor families. BSM recipients are students who have been determined by the Ministry of Education and Culture (Kemdikbud) based on the mechanism established has been determined. The ranking of beneficiaries can be done using a decision support system. The Simple Additive Weighting (SAW) method and the Weighted Product (WP) method have been widely used as support for decision making. results of both methods. Based on testing of 5 (five) students on the results of calculations using the Simple Additive Weighting (SAW) and Weight Product (WP) methods, the highest values ​​are different. From the SAW method, the highest result was obtained by Alternative 4, namely, Erik Kristanto. And from the WP method the highest results are shown in Alternative 3, namely, Rehulina G.